(untitled) (Ustozlar uchun, 2026)
This article examines the significance of the case study method in English language teaching and learning. The case study approach encourages students to develop critical thinking, problem-solving, communication, and collaborative skills while improving their language proficiency. By engaging learners in real-life situations, this method creates a learner-centered environment that enhances motivation and active participation. The paper discusses the educational value of case studies, their application in English language classrooms, and their contribution to developing communicative competence among students.